PENDIDIKAN ANAK DALAM KELUARGA - Irfan Syahroni, Muhammad (eJurnal Al Musthafa, 2024)
The family environment is the first and main place for children's education. It is the family that forms the character that will continue to imprint on the child for the future. A good education system must show the conceptual order of the educational process in the family as a realization of parents' responsibility for their children's education. These aspects such as worship, behavioral teachings, and education that increase children's intellectual, emotional, and spiritual intelligence. The success of education in school is highly dependent and influenced by education in the family. Children who are in a family that is not harmonious (broken home) will have a bad impact on children's learning achievements, behavior, and even mentality